2015
DOI: 10.1371/journal.pone.0140759
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diffusion Heterogeneity in Single Particle Tracking Trajectories Using a Hidden Markov Model with Measurement Noise Propagation

Abstract: We develop a Bayesian analysis framework to detect heterogeneity in the diffusive behaviour of single particle trajectories on cells, implementing model selection to classify trajectories as either consistent with Brownian motion or with a two-state (diffusion coefficient) switching model. The incorporation of localisation accuracy is essential, as otherwise false detection of switching within a trajectory was observed and diffusion coefficient estimates were inflated. Since our analysis is on a single traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…For example, not only do receptors diffuse, but their diffusion coefficient can randomly fluctuate (sometimes due to being trapped in membrane subdomains such as lipid rafts [80,65]). Two key examples are (i) LFA-1 receptors that alternate between fast and slow diffusive states [34,81] and (ii) AMPA receptors on the postsynaptic membrane that alternate within seconds between rapid diffusive and stationary states [16]. To extend the present work to such heterogeneous diffusion, one could assume the receptor diffusivity fluctuates between discrete states, as in [27,28,61].…”
Section: Comparison To Zwanzig Correctionmentioning
confidence: 99%
“…For example, not only do receptors diffuse, but their diffusion coefficient can randomly fluctuate (sometimes due to being trapped in membrane subdomains such as lipid rafts [80,65]). Two key examples are (i) LFA-1 receptors that alternate between fast and slow diffusive states [34,81] and (ii) AMPA receptors on the postsynaptic membrane that alternate within seconds between rapid diffusive and stationary states [16]. To extend the present work to such heterogeneous diffusion, one could assume the receptor diffusivity fluctuates between discrete states, as in [27,28,61].…”
Section: Comparison To Zwanzig Correctionmentioning
confidence: 99%
“…Specifically, models must approximate well the behaviour of different dynamic states in the data. For instance, confinement is often associated with a decrease in the effective diffusion coefficient, suggesting that models that switch diffusivities (25)(26)(27)(28)(29)(30) should also be able to detect confinement in these iSCAT particle trajectories. However, we found that a two-state diffusion coefficient switching HMM (30) could not segment these trajectories (data not shown).…”
Section: Outlook and Future Workmentioning
confidence: 99%
“…This has led to the development of a range of statistical methods that detect deviations from Brownian motion, such as mean square displacement (MSD) (8)(9)(10)(11)(12)(13), and confinement (14)(15)(16)(17)(18)(19) analyses. A new breed of methods model switching in the movement dynamics between various dynamic states (20)(21)(22)(23)(24), often within a hidden Markov chain framework (25)(26)(27)(28)(29)(30). For high resolution data the latter techniques can utilise the high level of information present in the trajectory to extract detailed motion characteristics, and potentially infer underlying biophysical mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, if one takes the switching rates to depend on spatial position, then in the fast switching limit one obtains Brownian motion with a space-dependent diffusivity of the Ito form. Advances in single-particle tracking (SPT) and statistical methods suggest that particles within the plasma membrane, for example, can switch between different discrete conformational states with different diffusivities [15][16][17]. Such switching could be due to interactions between proteins and the actin cytoskeleton [18,19] or due to protein-lipid interactions [20].…”
Section: Introductionmentioning
confidence: 99%